Power loss of the chain drive in a race tandem bicycle - Smit, A.; van der Zwaard, S.; Janssen, I.; Janssen, T. W. J. (Sports Engineering, 2023)
Tandem cycling is a paralympic discipline, in which two cyclists ride on one tandem bicycle. Their performance can be improved by minimizing power losses. This study aimed to quantify power loss due to the chain drive of a tandem bicycle and influence of power input, location of power input, and rear chain wheel size. Power loss was determined by the difference between power input applied on the cranks (front or back rider) and power output measured at the rear wheel. Power output values were set from 100 to 400 W, with 50 W increments, and using two gear ratios, 53-11 and 53-13. Power input was generated at the back crank (with only the primary chain—solo bicycle—and with primary and secondary chain attached) and at the front crank (with primary and secondary chain attached). The power loss for the solo bicycle was 2.1% (± 1.5%). A significantly larger power loss was found for the tandem in the back (3.7 ± 2.4%, p < 0.001) and front positions (3.0 ± 1.8%, p < 0.001), with marginal differences between positions at higher power output. Power loss for the tandem was lower with gear 53-13 (2.9% ± 1.7%) compared to 53-11 (4.0 ± 2.8%, p < 0.001, effect size is medium). Therefore, findings suggest that back and front riders experience similar power losses due to the chain drive, but more than on a solo bicycle. Tandem cyclists can reduce their power loss in the chain drive by selecting larger gear ratios. Coaches may consider these findings for selecting and coaching their tandem cyclists.